Exploring Structural Changes in Ge-Te Amorphous Films Through Small-Angle Neutron Scattering - Andrea A. Piarristeguy; Raphaël Escalier; Annie Pradel; Viviana Cristiglio; Gabriel J. Cuello (Applied Sciences)
The structure of the glassy GexTe1−x system, with x = 0.17, 0.21, 0.28, 0.30, and 0.45, is studied using the small-angle neutron scattering (SANS) technique. The very-low-momentum-transfer region of the diffractogram exhibits distinct behaviour depending on the germanium content. A similar conclusion is drawn from the analysis of the first diffraction peaks observed at higher angles. This system exhibits three composition regions with distinct behaviours: a first zone of low Ge content (up to about 20–25 at.%), a third zone richer in Ge (from about 30 at.% and above), and a second transitional zone between them. These changes are reflected in the parameters that govern Porod’s region, as well as in the region where the first diffraction peaks appear, corroborating previous observations made using other experimental and simulation techniques. Our study provides experimental evidence that could open up new possibilities for conducting simulations using neutron data. The results presented here show that increasing Ge content leads to a strengthening of the intermediate-range order at the expense of a weakening of the short-range order.